(untitled) (Issues in Social and Environmental Accounting (ISEA), 2026)
Climate change is no longer a distant threat; it is an immediate reality that poses significant risks to economies, ecosystems, and societies worldwide. In Canada, the implications of climate change are particularly pronounced, with rising temperatures and extreme weather events affecting everything from agriculture to urban infrastructure. A study published by the Canadian Institute for Climate Choices (2021) highlights that climate-related risks could cost the Canadian economy between CAD 21 billion to CAD 43 billion annually by 2050 if no action is taken. These figures underscore the urgency for businesses and policymakers to incorporate climate risk assessments into their strategic planning. Furthermore, the role of financial markets in reflecting these risks is crucial; as investors increasingly seek to understand the long-term viability of their portfolios, companies that fail to address climate risks may find themselves at a competitive disadvantage. This editorial note serves as a call to action for stakeholders to recognise the value relevance of climate change risks in their decision-making processes, thereby fostering a more resilient and sustainable future for all Canadians.